2019
DOI: 10.1037/pha0000270
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity and smoking outcome expectancies among Spanish-speaking Latinx adult smokers.

Abstract: Smoking is among the most important health behaviors linked to premature death and disability among the Latinx population. Yet there is limited understanding of whether transdiagnostic factors like anxiety sensitivity may help explain smoking expectancies among Spanish-speaking Latinx smokers. The present investigation evaluated anxiety sensitivity in regard to smoking outcome expectancy factors among a large sample of adult Latinx smokers. Participants were 363 Spanish-speaking Latinx daily smokers (58.7% fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Additionally, post hoc analyses indicated that when probable anxiety disorder was utilized as the anxiety phenotype predictor instead of the dimensional variable of anxiety symptom severity, the results remained consistent. Past research among Spanish-speaking Latinx smokers has found anxiety sensitivity to be related to negative and positive smoking outcome expectancies (Shepherd et al, 2022; Zvolensky, Bakhshaie, et al, 2019). The present findings extend such work to an English-speaking Latinx sample, distinguish the anxiety sensitivity effects from anxiety phenotypes (anxiety symptoms or probable anxiety disorder), and empirically document incremental validity relations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, post hoc analyses indicated that when probable anxiety disorder was utilized as the anxiety phenotype predictor instead of the dimensional variable of anxiety symptom severity, the results remained consistent. Past research among Spanish-speaking Latinx smokers has found anxiety sensitivity to be related to negative and positive smoking outcome expectancies (Shepherd et al, 2022; Zvolensky, Bakhshaie, et al, 2019). The present findings extend such work to an English-speaking Latinx sample, distinguish the anxiety sensitivity effects from anxiety phenotypes (anxiety symptoms or probable anxiety disorder), and empirically document incremental validity relations.…”
Section: Discussionmentioning
confidence: 99%
“…Participants are asked to rate the likelihood of each smoking-related consequence occurring on a 10-point Likert scale (0 = completely unlikely to 9 = completely likely ). The S-SCQ consists of four subscales and has well-demonstrated psychometric properties (Myers et al, 2003), including among Latinx smokers (Zvolensky, Bakhshaie, et al, 2019). The four subscales include negative consequences (e.g., “Smoking is taking years off my life.”), positive reinforcement (e.g., “When I smoke the taste is pleasant.”), negative reinforcement (e.g., “Cigarettes help me deal with anger.”), and appetite–weight control (e.g., “Cigarettes keep me from eating more than I should.”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, two independent stepwise linear regression models were conducted to examine fatigue severity and anxiety sensitivity in relation to negative expectancies and positive expectancies of e-cigarette use. Step 1 of each model included theoretically relevant covariates of age, sex, income, education, e-cigarette use frequency, and dual use status (Harrell et al, 2014; Hendricks et al, 2015; Pokhrel et al, 2014; Zvolensky et al, 2018b, 2019b). Step 2 included fatigue severity and anxiety sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…Within the available literature, there is evidence that greater anxiety symptoms, measured dimensionally, are associated with negative and positive outcome expectancies among Latinx Spanish-speaking smokers from the US [ 28 ] as well as greater perceived barriers for quitting and severity of interoceptive symptoms when trying to quit [ 29 ]. Related research has found that the cognitive factor of anxiety sensitivity, the belief that anxiety symptoms cause personal harm [ 30 ], is related to early smoking lapse among Latinx smokers from Mexico [ 31 ], negative and positive smoking outcome expectancies [ 32 ], as well as cigarette dependence and perceived barriers for quitting among Latinx Spanish-speaking smokers from the US [ 29 , 33 ]. Although anxiety symptoms and anxiety sensitivity are related, they are distinct constructs [ 34 ].…”
Section: Introductionmentioning
confidence: 99%